2007
DOI: 10.1038/ni1460
|View full text |Cite
|
Sign up to set email alerts
|

Syk- and CARD9-dependent coupling of innate immunity to the induction of T helper cells that produce interleukin 17

Abstract: The C-type lectin dectin-1 binds to yeast and signals through the kinase Syk and the adaptor CARD9 to induce production of interleukin 10 (IL-10) and IL-2 in dendritic cells (DCs). However, whether this pathway promotes full DC activation remains unclear. Here we show that dectin-1-Syk-CARD9 signaling induced DC maturation and the secretion of proinflammatory cytokines, including IL-6, tumor necrosis factor and IL-23, but little IL-12. Dectin-1-activated DCs 'instructed' the differentiation of CD4+ IL-17-produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

61
1,078
9
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,052 publications
(1,157 citation statements)
references
References 50 publications
61
1,078
9
9
Order By: Relevance
“…However, a partial defect in antigen processing cannot be formally excluded. Interestingly, PLCg2 À/À BMDC were less activated than WT BMDC also under steady state conditions, perhaps due to reduced function of other ITAMdependent receptors that are constitutively engaged during homeostasis.It has been shown that Syk and CARD9 promote secretion of cytokines such as IL-6 and IL-23 in response to b-glucan, generating the cytokine microenvironment that favors the expansion of T H 17 effector T cells [18,36]. In our study, PLCg2-deficient BMDC recapitulated both the Syk-deficient and CARD9-deficient phenotypes for Dectin-1-mediated responses.…”
supporting
confidence: 62%
See 2 more Smart Citations
“…However, a partial defect in antigen processing cannot be formally excluded. Interestingly, PLCg2 À/À BMDC were less activated than WT BMDC also under steady state conditions, perhaps due to reduced function of other ITAMdependent receptors that are constitutively engaged during homeostasis.It has been shown that Syk and CARD9 promote secretion of cytokines such as IL-6 and IL-23 in response to b-glucan, generating the cytokine microenvironment that favors the expansion of T H 17 effector T cells [18,36]. In our study, PLCg2-deficient BMDC recapitulated both the Syk-deficient and CARD9-deficient phenotypes for Dectin-1-mediated responses.…”
supporting
confidence: 62%
“…Thus, one would predict that lack of Syk and/or BTK in DC affects Dectin-1-mediated inflammatory cytokine production, as PLCg2-deficiency does. Accordingly, a previous study showed that lack of Syk impairs Dectin-1 function [8,9,18]. To further extend this study, we asked whether BTK is required for cytokine responses to b-glucan.…”
Section: Plcc2 Is Essential For Dectin-1-mediated Cytokine Productionmentioning
confidence: 90%
See 1 more Smart Citation
“…The requirement of the presence of DC is further supported by studies with murine bone marrowderived DC. DC stimulated by curdlan, a dectin-1 agonist, were found to effectively promote Th17 differentiation from CD4 1 T cells via an autonomous pattern recognition pathway [38]. However, to our knowledge the induction of Th17 by TLR-activated skin-DC, in our study substituted for methodical reasons by CD1c 1 MoLC, has not been reported before.…”
Section: Discussionmentioning
confidence: 48%
“…CARD9 is closely associated with immune responses, immune cell activation 3, 4 and inflammatory response 5. CARD9 utilizes B‐Cell lymphoma 10 (BCL10) and MALT1 to mediate Dectin‐1 signalling for the activation of nuclear factor‐k‐gene binding (NF‐κB), p38 mitogen‐activated protein kinase (p38 MAPK), and c‐Jun N‐terminal kinase (JNK) 2, 3.…”
Section: Introductionmentioning
confidence: 99%